Optimization of Valsartan Floating Tablets by 32 Factorial Design - Prasanthi, S. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The present study aimed at the development of valsartan floating tablets (VFTs) using Ocimum basilicum mucilage (OBM) and hydroxypropyl methylcellulose (HPMC) K100M by applying response surface methodology-based 32 factorial design. Materials and Methods: OBM (A) and HPMC K100M (B) were selected as independent factors, and swelling index (Y1) and time taken for 90% drug release (Y2) were as responses. Experimentally designed 9 runs assessed for Y1 and Y2, and analysis of variance (ANOVA) was applied (P < 0.05) to define significant terms. Multicriterion decision approach anticipated optimized formulation VFT was developed and evaluated for physicochemical parameters such as weight variation, hardness, friability, thickness, and drug content. In vitro drug release and buoyancy studies, in vivo buoyancy studies, and Fourier transform infrared (FTIR) studies were carried out along with the validation of experimental design. Results and Discussion: Synergistic effect between polymers was observed in experimental runs, and ANOVA indicated a significant effect of A and B on Y1 and Y2. Physicochemical parameters as well as floating lag time and total floating time of VFT were within the limits. FTIR studies unveiled drug and polymer compatibility. In vitro drug release studies demonstrated a good fit in zero-order and super Case-II transport drug release mechanism. Experimental values of VFT exhibited good agreement with predicted values generated by the software. In vivo buoyancy study in rabbit confirmed floatability of the VFT for 12 h. Conclusion: The present investigation concluded that statistically optimized VFT with OBM and HPMC K100M as rate retarding polymers exploiting as a promising formulation for gastric delivery of valsartan for longer periods.